Association Between Triglyceride-Glucose Index and Hypertension: A Meta-Analysis - Wang, Yi; Yang, Wei; Jiang, Xiao (Frontiers in Cardiovascular Medicine, 2021)
Background: Triglyceride-glucose (TyG) index is a recently proposed surrogate indicator of insulin resistance. Previous studies evaluating the association between TyG index and hypertension risk in general adult population showed inconsistent results. We performed a meta-analysis to systematically evaluate this association. Methods: Observational studies which evaluated the independent association between TyG index and hypertension in general adult population were identified by systematic search of PubMed, Embase, Web of Science, Wanfang data, and Chinese National Knowledge Infrastructure databases. A random-effect model which incorporated the potential intra-study heterogeneity was used for the meta-analysis. Results: Eight observational studies including 200,044 participants were included. Results showed that compared to those with the lowest category of TyG index, subjects with the highest category of TyG index were associated with higher odds of hypertension (adjusted risk ratio [RR]: 1.53, 95% confidence interval [CI]:1.26 1.85, I2 = 54%, P < 0.001). Sensitivity analysis by excluding one dataset at a time showed consistent result (adjusted RR: 1.44 1.62, P all < 0.001). Subgroup analyses showed that study characteristics such as study design, participant ethnicity, age, or sex of the participants did not significantly affect the association (P for subgroup difference all > 0.05). Conclusions: Higher TyG index may be associated with higher odds of hypertension in general adult population. Large-scale prospective cohort studies are needed to validate these findings, and further studies are needed to elucidate the potential pathophysiological mechanisms underlying the association between TyG index and hypertension.